2022
DOI: 10.1007/s11082-022-04068-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of downlink multipath multi-user NOMA-VLC system

Abstract: In the present paper, the performance of non-orthogonal multiple access (NOMA) in a downlink multipath multi-user Visible Light Communication (VLC) system has been evaluated w.r.t bit-error rate (BER), sum rate & outage probability. The results show that the sum rate and BER performance improve with the increase in semi-angle 𝝋 𝟏 𝟐 ⁄ of the LED using both Line-of-sight (LOS) and LOS plus first reflection (L-R1) signals. The simulation results display that there is optimal value of 𝝋 𝟏 πŸβ„ at which minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Closed-form expressions for the bit error rate (BER) of NOMA-VLC systems with on-off keying (OOK) and L-ary pulse position modulation have been derived, considering perfect and imperfect channel state information [14]. The results of [15] demonstrated that the performance metrics (BER, sum rate, and outage probability) in a multi-user NOMA-VLC system can be affected by the number of users, signal type, and shadowing under different half-angles of LEDs and signal reflection path conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Closed-form expressions for the bit error rate (BER) of NOMA-VLC systems with on-off keying (OOK) and L-ary pulse position modulation have been derived, considering perfect and imperfect channel state information [14]. The results of [15] demonstrated that the performance metrics (BER, sum rate, and outage probability) in a multi-user NOMA-VLC system can be affected by the number of users, signal type, and shadowing under different half-angles of LEDs and signal reflection path conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmood et al [15], Hassan et al [23], and Kumar et al [25] a power domain NOMA system is tested. The BER performance is evaluated on Stanford University Interim (SUI) fading channel models considering a various number of users per-cluster in suburban environments.…”
Section: Introductionmentioning
confidence: 99%